THE IMPACT OF ESG ON STOCK PRICE VOLATILITY: FIRM SIZE AS MODERATING VARIABLE (An Empirical Study on Indonesian Manufacturing Companies Listed on the IDX during the Year 2021-2024) - Ananda Raisa Indira; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on stock price volatility and examine the role of firm size as a moderating variable. The independent variable in this study is ESG disclosure, measured using content analysis methods, and the dependent variable is stock price volatility. Return on Assets (ROA) and leverage, measured using the Debt to Equity Ratio (DER), serve as control variables.            The population of this study was manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. The sample selection used a purposive sampling method, with a total of 288 observations meeting the research criteria. The research approach used a quantitative method with panel data regression using the Random Effects model, and MRA to test the moderating role of firm size. A sensitivity analysis is also carried out by decomposing the ESG score into its environmental, social, and governance dimensions.            The results show that although the coefficient for ESG disclosure on stock price volatility is negative, the effect is not statistically significant. This indicates that higher ESG disclosure, when aggregated, does not consistently lead to lower stock price volatility. Firm size also does not strengthen the negative relationship between ESG disclosure and stock price volatility; instead, the interaction terms suggest that any potential risk-reducing effect of ESG tends to weaken as firm size increases. The sensitivity analysis further reveals that only social disclosure has a negative and significant impact on volatility, while environmental and governance disclosures are not significant. These findings imply that investors respond more social-related information than to ESG performance as a whole.